Character Values of Dewi Siti Sarijati's Oral Stories in Sluke Village, Rembang Regency - Mohammad Kanzunnudin; Ahdi Riyono; Noor Rina Kastatria; Arceli R. Millan (UIN Raden Mas Said Surakarta, Indonesia, 2025)
Sluke Village, Sluke District, Rembang Regency, Central Java, is a coastal area. The characteristics of coastal areas produce a culture in the form of folklore with various forms, such as fairy tales, proverbs, parikan (pantun), and seloka. One of the oral folklore that is very famous and has not been studied by other researchers from the perspective of character values, namely the oral story